Comparison of IC50 and AAI Value of Ethanol Extract Kopasanda Leaves (Chormolaena Odorata) as an Antioxidant using the DPPH Method for Percolation and Sockletation Extraction - Abanit, Yohanes M.; Tjitda, Putra J.P.; Soeharto, Faizal R.; Londa, Mathilda K. (Indonesian Journal of Global Health Research, 2023)
The Kopasanda plant is a plantplant species that are easily found in various places that have themefficacy as an antioxidant.Objective: to determine the antioxidant value of the ethanol extract of kopasanda leaves using the DPPH method of percolation and soxhletation extraction which is expressed using IC50 and AAI in a quantitative descriptive manner. Kopasanda leaves were extracted using the percolation and soxhletation method with 70% ethanol solvent and phytochemical screening and antioxidant activity of the extract were carried out using the DPPH method. Data analysis uses linear regression testing. The phytochemical screening test showed that the ethanol extract of kopasanda leaves contained positive flavonoids, saponins, tannins and alkaloids. The average percent reduction of DPPH by the perchloation extraction method at concentrations of 40 ppm and 120 ppm: 40.87% and 63.94%, while the soxhletation extraction method: 39.82% and 67.42%. The average IC50 value of the ethanol extract of kopasanda leaves for the percolation extraction method: 74.1081 ppm and the soxhletation extraction method:68.1975 ppm. The results of the antioxidant activity test of kopasanda leaves using the DPPH method for percolation and soxhletation extraction are included in the strong antioxidant category with a medium antioxidant index.